A Case of Secondary Infertility Due to Retention of Fetal Bones in Cervix - Özer, Serdar; Özer, Alev; Kanat Pektaş, Mine; Özakşit, Gülnur (Gynecology Obstetrics & Reproductive Medicine, 2011)
A case of secondary infertility related with prolonged retention of fetal bones in cervix is presented. A 34-year-old nulliparous woman admitted to hospital with chronic pelvic pain, dyspareunia and 12-yearlong secondary infertility following an induced abortion due to fetal demise. Transvaginal ultrasonography (USG) revealed a linear echogenic area around the posterior cervical wall. Hysteroscopic examination confirmed the existence of an irregular calcified mass embedded in cervix. The mass turned out to be conglomerated fetal bone fragments which probably acted as an intrauterine device. After removal of the cervical mass, the patient conceived spontaneously within four months. The present case report emphasizes the significance of detailed history and through evaluation by transvaginal USG in case of secondary infertility following an induced or spontaneous abortion.